Alkyl Halides as Substrates for Photocatalytic Minisci-Type C–H Alkylation of Hetarenes - Predygier, Jędrzej; Szczepanik, Joanna; Giedyk, Maciej (Synlett, 2021)
Alkyl halides are readily available starting materials for various synthetic transformations, including Minisci-type C–H functionalizations of hetarenes. The existing methods, however, often require harsh reaction conditions, such as the use of acids, sacrificial electron donors, or radical precursors in excess amounts. Here, we outline recent developments in this field and we highlight our group̓s efforts to achieve fully catalytic photoredox Minisci-type alkylations supported by noncovalent interactions under mild aqueous conditions.
Keywords: C–H functionalization; Minisci reaction; alkyl bromides; hetarenes; photoredox catalysis; alkylation